The Influence of Memory Strategy used with Classical Music on Students’ Capability in Memorizing Vocabulary - Meiliana, Dea; Satria, Irwan; Martina, Feny (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
The aim of this research is to determine the effect of memory strategies using classical music on the ability to memorize vocabulary in class VIII students at SMPN 2 Pasemah Air Keruh. The method in this research is a quantitative method with an experimental research type. This research was conducted with two groups, namely the experimental class taught using memory strategies using classical music and the control class taught without using memory strategies using classical music. The population in this study was class VIII students at SMPN 2 Pasemah Air Keruh, totaling 88 students with a sample of 60 students (30 experimental class students and 30 control class students). In the first step, the researcher gave a pre-test to the experimental class and the control class. After that, the researcher gave a post-test to the experimental class and the control class. Pre-test and post-test scores are collected from multiple-choice questions. Then it was analyzed using SPSS 26. The findings of this research showed that the average score for the experimental class from the pre-test was 52.5 and the post-test was 81.0. Next, the hypothesis test obtained a 2-tailed sig (p) of 0.00 while alpha (a) was 0.05 (0.00<0.05). This means that Ho is rejected and Ha is accepted. So, it can be concluded that the use of memory strategies using classical music has a significant influence on students’ ability to memorize vocabulary.